1991
DOI: 10.1029/91je00976
|View full text |Cite
|
Sign up to set email alerts
|

A control network of Triton

Abstract: A control network for Triton has been computed using a bundle-type analytical triangulation program. The network contains 105 points that were measured on 57 Voyager 2 pictures. The adjustment contained 1010 observation equations and 382 normal equations and resulted in a standard measurement error of 13.36 /am. We determined coordinates of the control points, the camera orientation angles at the times when the pictures were taken, and Triton's mean radius. A separate statistical analysis confirmed Triton's ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Treating uncertainty in the focal length (1503.49 ± 0.39 mm or 2.59 × 10 −4 ; Davies and Katayama 1981) as an independent effect combined with the measurement uncertainty of 5.9 × 10 −4 , absolute values of radii are estimated to have uncertainties of 6.46 × 10 −4 or 0.9 km. The mean radius solution, 1353.4 ± 0.9 km, is well within uncertainties of the mean radius found by Davies et al (1991) using control points, 1352.6 ± 2.4 km, and with the radio science results of 1355 ± 7 (Tyler et al 1989) and 1351 km (Marouf et al 1991).…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…Treating uncertainty in the focal length (1503.49 ± 0.39 mm or 2.59 × 10 −4 ; Davies and Katayama 1981) as an independent effect combined with the measurement uncertainty of 5.9 × 10 −4 , absolute values of radii are estimated to have uncertainties of 6.46 × 10 −4 or 0.9 km. The mean radius solution, 1353.4 ± 0.9 km, is well within uncertainties of the mean radius found by Davies et al (1991) using control points, 1352.6 ± 2.4 km, and with the radio science results of 1355 ± 7 (Tyler et al 1989) and 1351 km (Marouf et al 1991).…”
Section: Methodsmentioning
confidence: 78%
“…The mean radius solution corresponds to a mean density of 2.06 ± 0.01 g cm −3 (mass of Anderson et al 1991), a value indistinguishable from that using the radius found by Davies et al (1991). A synchronously rotating, homogeneous satellite in hydrostatic equilibrium of this density in Triton's orbit with a mean radius of 1353.4 km should have a polar flattening of 1.8 km (see Chandrasekhar 1969).…”
Section: Interpretationsmentioning
confidence: 93%
See 1 more Smart Citation
“…The solar phase function of Goguen et al (1989) was assumed for reduction of V observations, and B and I observations as well. The geometric albedos in V were computed using −26.75 for the apparent V magnitude of the Sun (Livingston, 2000) and 1352.6 km as the radius of Triton (Davies et al, 1991). We use this radius rather than the more recently determined radius of 1353.4 km (Thomas, 2000) to be consistent with earlier workers.…”
Section: Triton Photometrymentioning
confidence: 64%
“…An incredible scientific harvest indeed for science and for the public. Davies accomplished his objectives of establishing control nets for not only the large Galilean Moons of Jupiter but for nearly all of the significant moons orbiting Saturn and Uranus, and even Neptune's moon Triton, at the very edge of the domain of planets (Davies, Rogers, and Colvin, 1991). During the 1990s, Voyager's legacy was further augmented by the rich new data sets returned by the Galileo Orbiter mission for Jupiter, in which Davies also participated.…”
mentioning
confidence: 99%